Demand versus supply side climate policies with a carbon dioxide ceiling - Thomas Eichner; Gilbert Kollenbach; Mark Schopf (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2018)
Consider a dynamic model with two countries or coalitions that consume and trade fossil fuel. A non-abating country owns the entire fuel stock and is not concerned about climate change, represented by a ceiling on the carbon dioxide concentration. The government of the other country implements public policies against global warming, either by capping domestic fuel consumption or by buying deposits to postpone their extraction. The demand [supply] side policy is inefficient because the consumers [suppliers] in the nonabating country do not internalize the climate externality. In particular, at the demand side policy aggregated fuel consumption is inefficiently low [high] in the climate coalition [non-abating country]. If strategic price incentives are strong, the coalition further depresses its fuel consumption to reduce the fuel price and hence its fuel import bill. At the deposit policy, the fossil fuel consumption and price paths are discontinuous when the ceiling becomes binding and the coalition takes over complete fuel supply. If strategic price incentives are strong, the coalition decreases its deposit purchases to reduce the fuel and the deposit price. If the coalition is the sole fuel supplier, it reduces its extraction to raise the fuel price in a monopolistic fashion.
Keywords: F55; H23; Q54; Q58; 330; Demand Side Policy; Supply Side Policy; Climate Change; Deposit; Fossil Fuel